Flows under stress: Availability of plant genetic resources in times of climate and policy change - López Noriega, Isabel; Galluzzi, Gea; Halewood, Michael; Vernooy, Ronnie; Bertacchini, E.; Gauchan D; Welch, Eric W. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2012)
There is growing recognition that successful adaptation of agricultural production systems to changes in climate will depend upon the improved access to, and use of, genetic diversity. In order to facilitate this adaptation, new forms of interdisciplinary research, new technologies, novel partnerships and effective policy instruments are considered essential. Given their mandate, history and expertise, the centres of the Consultative Group on International Agricultural Research (CGIAR Centres) are expected to play an important role in developing novel agricultural research strategies required to respond to climate change challenges. This report describes how eight of the CGIAR Centres whose research is focused on plant genetic resources, are (re)organizing their conservation and improvement activities in light of climate change adaptation. The report also analyzes how the collection, use and distribution of plant genetic resources by CGIAR Centres are influenced by international and national policies, treaties and agreements. The study concludes that climate change has not radically changed CGIAR gene bank and plant-breeding priorities and approaches, although it has added some urgency to changes already occurring in the CGIAR system. In recent years, the CGIAR Centres have broadened their operational strategies through closer co-operation with the private sector and through more direct interactions with farmers, national extension agencies, non-government organizations and aid agencies. Explicit climate change adaptation efforts related to plant genetic resources can be found in the operational strategies of some of the centres and for some crops, but, to date, no specially developed system-wide strategy has been developed. The most significant changes that are occurring are more strongly influenced by demand from the donor and international development community for more impact ‘on the ground.’ Some concerns exist among CGIAR scientists about continued access to plant genetic resources, including crop wild relatives. Such access is important for the discovery and use of climate-relevant traits. CGIAR scientists also expressed concerns about the distribution of plant genetic resources which in recent years has become subject to new rules and regulations. Study findings point to an increasing influence of international and national policies and legal frameworks on all of the operations of the CGIAR Centres from upstream to downstream levels. It appears that, broadly considered, recent changes in the policy environment are not having significant positive impacts on the efforts that the centres and their partners are making to continuously access and use plant genetic resources. This situation may, in the longer term, have a serious impact on the development of (new) strategies to adapt to climate change that are based on the use of plant genetic resources.